The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1590/fst.108421
|View full text |Cite
|
Sign up to set email alerts
|

Prepparation, characterization and antioxidant activity of polysaccharides selenides from Qingzhuan Dark Tea

Abstract: The effective selenylated polysaccharides (refer as TPS-Se) with an average molecular weight (M W ) of 3.109 × 104 Da was synthesized by the reduction of sodium selenite with ascorbic acid in the presence of Qingzhuan Dark Tea polysaccharides (TPS). The selenium (Se) content of TPS-Se was up to 37.05%. The differences between TPS and TPS-Se were compared in morphology, structure, antioxidant activity, and molecular weight using FT-IR, Raman spectroscopy, X-ray diffraction (XRD), and X-ray photoelectron spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…And the possible regulatory pathways of tea on glucolipid metabolism were as follows: inhibiting lipid absorption by forming complex with lipids and lipases (Xu et al, 2020), reducing glucose digestion and absorption by inhibiting amylase activity (Sun et al, 2017), inhibiting gluconeogenesis (Collins et al, 2007), enhancing glucose consumption and utilization (Lin & Lin, 2008) etc. Of course, researchers suggested that tea polyphenols (TPs) (Macena et al, 2022;Tan et al, 2022), caffeine (CAF), tea polysaccharide (Zhou et al, 2022a(Zhou et al, , 2023Kim et al, 2022), and other functional ingredients (Rubanka et al, 2020;Wang et al, 2023) contained in tea play a key role in lowering blood glucose levels. In addition, studies suggested that TPs (Zhou et al, 2022b), tea pigment (Liu et al, 2020) and other functional components contained in tea also play an important role in lowering uric acid levels.…”
Section: Introductionmentioning
confidence: 99%
“…And the possible regulatory pathways of tea on glucolipid metabolism were as follows: inhibiting lipid absorption by forming complex with lipids and lipases (Xu et al, 2020), reducing glucose digestion and absorption by inhibiting amylase activity (Sun et al, 2017), inhibiting gluconeogenesis (Collins et al, 2007), enhancing glucose consumption and utilization (Lin & Lin, 2008) etc. Of course, researchers suggested that tea polyphenols (TPs) (Macena et al, 2022;Tan et al, 2022), caffeine (CAF), tea polysaccharide (Zhou et al, 2022a(Zhou et al, , 2023Kim et al, 2022), and other functional ingredients (Rubanka et al, 2020;Wang et al, 2023) contained in tea play a key role in lowering blood glucose levels. In addition, studies suggested that TPs (Zhou et al, 2022b), tea pigment (Liu et al, 2020) and other functional components contained in tea also play an important role in lowering uric acid levels.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, TPS had been very active in international scientific community, especially in the fields of nutrition, pharmacy and food science, among which the development of metal ion complexation of TPS is one of the research hotspots (Liu et al, 2018;Mei et al, 2017;Huang et al, 2017). Compared with TPS, its complexation with iron ions and selenium ions had enhanced the antioxidant properties (Zhou et al, 2022a(Zhou et al, , 2022bAlmanaa et al, 2022;León et al, 2022), and its complexation with scandium was used in various tumors such as MNNG/HOS osteosarcoma, A375 melanoma, A549 Lung adenocarcinoma, U251 glioma, etc. with antiproliferative properties and as a nuclear medicine theragnostic agent (Mazza et al, 2021;Muñoz-Garcia et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, interest in tartary buckwheat tea (TBT) has also increased because of its health benefits and convenience. Unlike traditional tea products (green teas and black teas), TBT is strictly a grain tea, a substitute tea made from tartary buckwheat seeds and other raw materials (Qin et al, 2013;Tang et al, 2019;Zhou et al, 2022). Total flavonoid content in the tea infusion of TBT, which is rich in flavonoids, can be used as a source of rutin in the human diet (Xu et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%